Emerging Developments in Management of Melanoma During the COVID-19 Era - Li, Andraia R.; Valdebran, Manuel; Reuben, Daniel Y. (Frontiers in Medicine, 2021)
In March 2020, the designation of the COVID-19 outbreak as a worldwide pandemic marked the beginning of an unprecedented era in modern medicine. Facing the possibility of resource precincts and healthcare rationing, leading dermatological and cancer societies acted expeditiously to adapt their guidelines to these contingencies. Melanoma is a lethal and aggressive skin cancer necessitating a multidisciplinary approach to management and is associated with significant healthcare and economic cost in later stages of disease. In revisiting how the pandemic transformed guidelines from diagnosis and surveillance to surgical and systemic management of melanoma, we appraise the evidence behind these decisions and their enduring implications.